PREVALENCE OF VENEREAL DISEASE IN THE BLOOD DONOR AND ITS ASSOCIATION WITH EDUCATION LEVEL: AN EXPERIENCE FROM A TERTIARY CARE HOSPITAL (Journal of Medical & Health Sciences Review, 2025)
Objective: To determine the prevalence of venereal diseases, HIV and syphilis, in blood donors and to determine association of positive cases of venereal diseases with education level of donors.Material and Methods: this is cross-sectional descriptive study, extended for eighteen months, in which 1962 healthy donors were enrolled. Screening for HIV was done by Microparticle enzyme immunoassay and Chemiluminescent immunoassay techniques. Syphilis screening was done by Treponema Pallidum particle agglutination and Chemiluminescent Imunoassay methods. Patient’s data were analyzed using SPSS. Descriptive statistics were computed. Association of disease with education was observed by using chi square test. The stratification was done. P-value ≤0.05 was considered as significant.Results: Among 1962 donors 1960 (99%) were males and 2 (0.1%) were females with mean age of 29.8 +- 7. In our study 35 (1.8%) donors were found positive for syphilis and 2 (0.1%) were positive HIV I and II. There was significant association of syphilis with education (p=0.041), majorly having secondary education.Conclusion: The prevalence of syphilis was noted to be very high as compared to HIV in blood donors. There was strong association with secondary education level.